Genus Microlithosia (Lepidoptera, Erebidae, Arctiinae) in Laos, with the description of a new species - Bayarsaikhan, Ulziijargal; Lee, Dong-June; Bae, Yang-Seop (Zootaxa, 2018)
Microlithosia Daniel, 1954 from Laos is reviewed. A new species, Microlithosia laosana Bayarsaikhan & Bae, n. sp., is described along with two newly recorded species, M. umbripuncta (de Joannis, 1928) and M. nanlingica Dubatolov, Kishida & Wang, 2012. Illustrations of adults and male genitalia are provided. The checklist of the genus is updated.